Comparative Analysis of Delamination Factor in CNC Drilling of Novel Kenaf Fiber Reinforced Aluminum Wire Mesh Sandwich Composite and Kenaf Fiber Laminate with 45o /0o /45o Ply Orientation Angle (Journal of Pharmaceutical Negative Results, 2022)
Aim: This research is to compare and analyze the delamination factor in CNC drilling of novel kenaf fiber reinforced with aluminum wire mesh sandwich composite and kenaf fiber laminate with (45o /0o /45o ) ply orientation angle.Material and Methods: During the drilling of kenaf fiber reinforced composite, Delamination is a severe problem. The goal of this research is to determine the effect of cycle boundaries on delamination during penetration of (50%) kenaf fiber and (80%) epoxy supported aluminum wire mesh. The kenaf fiber reinforced composite was made using the hand layup process (kenaf+aluminum+kenaf+aluminum+kenaf). A tungsten carbide drilling device with an 8mm diameter was used to drill the manufactured sample. Feed rate (mm/rev), Speed rate (rpm) and drill bit diameter (mm) are the process characteristics that have been considered. The Celestron microcapture software was used to investigate the data collected by taking advantage of the various quantifiable metrics and graphs available. Sample sizes for each group were 20 with pre-test power of 80%, beta=0.05%, and CL 95%. Results: An experimental scan with 20 samples per group is chosen and the delamination factor was scaled for both the working sample and the analysis. During this examination, CNC bores and delamination factors were determined. The results obtained for independent T test statistical analyses in SPSS software was 0.025 (P<0.050). Conclusion: Within the limitations of this study, the analysis of Kenaf fiber laminate with (45o /0o /45o ) ply orientation angle has produced a delamination factor of of 1.38949 for the samples reinforced with Aluminium mesh and the mean delamination factor of 1.65830 for samples reinforced without Aluminium mesh with an improvement of 16.2% in reducing delamination factor comparing base materials.